Ethnobotany of the Kombong Agroforestry System and Tongkonan Conservation in the Toraja Tribe, South Sulawesi, Indonesia - Millang, Syamsuddin; Yuniati, Eny; Paembonan, Samuel A.; Arty, Budi; Makkasau, Ahmad R. (Forest and Society, 2024)
The Kombong agroforestry system (KAS) has long been practiced and plays an important role in the livelihoods of the Toraja tribe's settlements, in addition to their social, cultural, and environmental sustainability. This research aims to explain the species composition and wood volume, how the utilization of plant species in the KAS has social, cultural, economic, and ecological functions, analyze the plant cultural significance of KAS of the Toraja tribe, the role of KAS for the conservation of Tongkonan Traditional Houses (TTHs) and KAS in preserving the Rambu Tuka' and Rambu Solo’ traditional ceremonies of the Toraja tribe. The research used vegetation survey methods and in-depth interviews with respondents, which were conducted using a set of guidelines for questionnaires. The research results indicate that there are 115 plant species belonging to 49 families. The plant use category is high, with foodstuffs and fruit being the use category with the highest number of species. The index of cultural significance (ICS) of the Toraja tribe varies greatly, from very high categories to those whose use is not yet known. Rice has the highest ICS value, with a score of 130. The KAS and TTHs are closely related and are always found in traditional Toraja settlements. They form a unit that supports each other, and the existence and sustainability of a TTH largely depend on the preservation of the KAS. The KAS has a close connection to both the Rambu Solo' and Rambu Tuka' traditional ceremonies. All plant species needed to build and maintain a TTH and for conducting these two traditional ceremonies are found in the KAS. Thus, the KAS is very important for the Toraja tribe because it not only supports the economic and social aspects of their lives but also functions to protect the environment and traditional culture, including preserving the TTH form and the Rambu Solo' and Rambu Tuka' traditional parties.